Translating the Nation: Rizal, the Novel and Philippine Literatures in the Regions - Garcia, University of the Philippines, Diliman, J. Neil C. (Asiatic: IIUM Journal of English Language and Literature, 2011)
Legislated as the official national myth in the Philippines, the revolutionary novels of the foremost Filipino hero, Jose Rizal, continue to be taught across the secondary and tertiary levels in the Tagalog-based language of Filipino. Together with English, Filipino enjoys a distinct advantage as a fully developed literary language in the country, even as the many other languages of the archipelago are slowly and inexorably sliding into desuetude and neglect. Arguing that translation is at once a metaphorical and appropriative act, the author proposes that Rizal’s already inescapably translational texts be made available to Filipino students in their own mother tongues, in recognition of their evocative power (that includes rather than excludes) on one hand, and in order to more fully realize Rizal’s vision of an emancipated national body, on the other.